1994
DOI: 10.1128/jb.176.7.1872-1880.1994
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning of chromosome I DNA from Saccharomyces cerevisiae: analysis of the genes in the FUN38-MAK16-SPO7 region

Abstract: Transcribed regions on a 42-kb segment of chromosome I from Saccharomyces cerevisiae were mapped.Polyadenylated transcripts corresponding to eight previously characterized genes (AL4K16, LTE1, CCR4, FUN30, FUN31, TPD3, DEPI, and CYS3) and eight new genes were identified. All transcripts were present at one to four copies per cell except for one which was significantly less abundant. This region has been sequenced, and the sizes, locations, and orientations of the transcripts were in nearly perfect agreement wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
38
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 61 publications
0
38
1
Order By: Relevance
“…However, unlike Ntg2p and all other known endo III homologs, Ntg1p does not possess a C-terminal Fe-S cluster (40). In addition, Ntg1p has a putative mitochondrial targeting sequence, while Ntg2p does not (2,40). Finally, although recent studies have demonstrated that the expression of NTG1 is induced by H 2 O 2 (11,40), expression of NTG2 does not appear to be H 2 O 2 inducible (40).…”
mentioning
confidence: 76%
“…However, unlike Ntg2p and all other known endo III homologs, Ntg1p does not possess a C-terminal Fe-S cluster (40). In addition, Ntg1p has a putative mitochondrial targeting sequence, while Ntg2p does not (2,40). Finally, although recent studies have demonstrated that the expression of NTG1 is induced by H 2 O 2 (11,40), expression of NTG2 does not appear to be H 2 O 2 inducible (40).…”
mentioning
confidence: 76%
“…Transcription of NTG1 (termed FUN33) has been demonstrated by Barton et al (27) who made a survey of all the genes present in this region on chromosome I in S. cerevisiae. The transcript of NTG1 was estimated to about 1.3 kb and the level of the transcript was found to be fairly low.…”
mentioning
confidence: 99%
“…We found that one of the hits is an evolutionarily conserved Snf2 ATPase, Fun30 (Function unknown now 30). Fun30 was initially identified and named by yeast chromosome I cloning and sequencing projects (25,26). Previous studies have implicated a role of Fun30 and its higher eukaryotic homolog Fft3 (pombe) or SMARCAD1 (mammalian) in promoting heterochromatin silencing (27)(28)(29)(30).…”
mentioning
confidence: 99%